Antioxidant Properties Of N-Hexane Extract From Tobacco Leaves (Nicotiana tabacum L.) Using 2,2-Diphenyl-1-Picrylhydrazil (DPPH) Method - Patricia, Vinda Maharani; Az-zahra, Dhea Khairunnisa; Fakih, Taufik Muhammad; Suarantika, Farendina (Pharmacology and Clinical Pharmacy Research, 2025)
Tobacco (Nicotiana tabacum L.) is a commercial plant that often used for making cigarettes. In 2012, the government issued regulations for the diversification of tobacco products besides cigarettes. Some of these diversified tobacco products include organic pesticides, anesthetics, cosmetic ingredients, and biochar as an alternative to coal. Therefore, in order to further to diversification of tobacco product, this study aimed to determine the antioxidant activity from n-hexane extract from leaves using the Soxhlet extraction method. Antioxidant activity was assessed by the DPPH (2,2-diphenyl-1-picrylhydrazyl) method, while the total phenolic content was determined using the Folin-Ciocalteu method that allowed quantification of phenolic compounds in the extract, which possesses the role of antioxidant. The IC50 value obtained from the antioxidant activity assay of the n-hexane extract of tobacco leaves was 426.042 μg/mL, classified as very weak. Meanwhile, the total phenolic content was 51.93 mg GAE/g. These results suggest that the high total phenol content may have other potential activities that can be tested, such as antibacterial activity.